Budaya Sekolah: " Ngumpulke Balung Pisah" Melalui Pengajaran Multikultur - Abd. Jabar, Cepi Safruddin (Dinamika Pendidikan, 2001)
Budaya Sekolah: " Ngumpulke Balung Pisah" Melalui Pengajaran Multikultur